Unlocking the Power of Traditional Medicinal Plants: The Need for Standardization and Promotion of Herbal Extracts - KK, Mueen Ahmed (Pharmacognosy Reviews)
In recent years, there has been a resurgence of interest in traditional medicinal plants, driven by growing concerns about the side effects of synthetic medicines and the increasing burden of chronic diseases. The comprehensive reviews of various medicinal plants, including Sea buckthorn, Guava, selected traditional medicinal plants, Withania coagulans, and Desmodium canum, highlight the vast potential of these natural resources in modern medicine. However, despite the promising pharmacological actions and medicinal properties of these plants, their full potential remains untapped due to a lack of standardization and promotion of herbal extracts. In this editorial, I argue that standardization and promotion of herbal extracts are crucial for unlocking the power of traditional medicinal plants and ensuring their safe and effective use in modern medicine.